Case report: Rare restrictive cardiomyopathy with ventricular fibrillation as initial symptom rescued by automatic external defibrillator in a pediatric patient - Ji, Lianfu; Chen, Jinlong; Qin, Yuming; Yang, Shiwei (Frontiers in Cardiovascular Medicine, 2022)
Restrictive cardiomyopathy (RCM) is a rare form of heart muscle disease with poor prognosis. Its primary manifestations were caused by systemic or pulmonary circulation congestion. Here, we reported a case of RCM with ventricular fibrillation as initial symptom in a 7-year-old boy. The child suffered cardiac and respiratory arrest suddenly while exercising at school and immediately was given external chest compression and defibrillation by the school’s equipped automatic external defibrillator (AED). The rescue was successful. At the time of the AED discharge, his electrocardiogram (ECG) indicated ventricular fibrillation. Upon further examination, the echocardiogram revealed enlarged bilateral atria, decreased diastolic function and normal ventricular thickness. Genetic analysis identified a heterozygous missense mutation [c.611(exon8)G>A,p.R204H] of TNNI3 in the proband boy. This case contributes to our understanding of RCM in children and emphasizes the importance of having AEDs available in public places.